2017
DOI: 10.9790/487x-1906026270
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Performance-Based Budgeting System Implementation in Improving Organizational Effectiveness

Abstract: Abstract. This study aimed to: 1) investigate and analyze the implementation of performance-based budgeting system in the Regional Secretariat of Wakatobi District: 2) analyze the organizational effectiveness in the Regional Secretariat of Wakatobi District. Object of the study was the Regional Secretariat of Wakatobi District. Population of the study was all staff at the Regional Secretariat of Wakatobi regency. Informants are determined through purposive sampling method using the following criteria: 1) knowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Lastly, plans will be thwarted if the budget is ineffective and not performance-oriented. Thus, the budget is a managerial plan for actions that facilitate achieving organizational goals (Liwaul et al, 2017) Several related studies suggested implementing PBB improved government financial performance (Dewata et al, 2022;Oktavia, 2017;Sofyani, 2018). In addition to the central government, the implementation of PBB also improved regional financial performance and budget efficiency.…”
Section: Theoretical Reviewsmentioning
confidence: 99%
“…Lastly, plans will be thwarted if the budget is ineffective and not performance-oriented. Thus, the budget is a managerial plan for actions that facilitate achieving organizational goals (Liwaul et al, 2017) Several related studies suggested implementing PBB improved government financial performance (Dewata et al, 2022;Oktavia, 2017;Sofyani, 2018). In addition to the central government, the implementation of PBB also improved regional financial performance and budget efficiency.…”
Section: Theoretical Reviewsmentioning
confidence: 99%
“…Similarly, the Indonesian government has introduced the performance‐based Budgeting System which requires public agencies to prepare strategic plans, delineate performance measures, and submit performance reports (Liwaul & Hamryati, 2017). In Singapore, the budgeting for results also focuses on public sector performance in terms of final outcomes.…”
Section: Impacts Of Entrepreneurship‐led Reforms On Public Accountabimentioning
confidence: 99%
“…Buku panduan tersebut mensyaratkan semua PTM mengelola keuangan yang mengacu pada anggaran berbasis kinerja pada saat menyusun rencana anggaran pendapatan dan belanja (RAPB). Anggaran berbasis kinerja merupakan sistem penganggaran yang mengukur luaran program kerja (Ninik & Purwati, 2017). Luaran anggaran berbasis kinerja tidak hanya laporan realisasi anggaran melainkan laporan keuangan yang terdiri dari posisi keuangan, aktivitas dan arus kas (Oktavia, 2017).…”
Section: Pendahuluanunclassified
“…Sebelum materi disampaikan, semua peserta dibagikan angket pengetahuan dalam bentuk perntaan multiple choice untuk mengetahui sejauh mana pemahaman mereka tentang anggaran berbasis kinerja (Ninik & Purwati, 2017). Sesi ini bertujuan memperkenalkan kepada peserta panduan dalam menyusun anggaran berbasis kinerja (performance based budgeting).…”
Section: Pengenalan Anggaran Berbasis Kinerja (Performance Based Budgeting)unclassified